THE ETHNICPOLITICAL CONTRADICTIONS AND CONFLICTS THAT HAPPENED IN WESTERN UKRAINE (1926-1939) - Гон, М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article gives analysis of the ethnicpolitical conflicts which took part on the West of Ukraine which belonged to Poland. The contradictions between “our” and “strangers” are studied in the context of interests and adaptations. Among them – the struggle of Polish and Ukrainian people for preserving/restoring their sovereignty on the territory, different views of ethnic communities concerning the decentralization of ruling the country, inequality of ethnic groups in the country ruling. The author suggests that these contradictions should be considered as the result of aversion of the political symbols of “strangers”. This, according to the author, is the element of semiotic conflict. He considers it to be a specific type of ethnic conflict. The article also analyses the influence of outer political factors on the formation of the relations between different ethnic groups.